UPAYA MENINGKATKAN KEMAMPUAN KOGNITIF ANAK KELOMPOK B MELALUI PERMAINAN DADU DANCE DAN BOLA BLAST DI RA TARBIYATUL IHSAN LEMAH KEMBAR - Sriwijayanti; Eka Dheasari, Agustiarini (LPPM IAD Probolinggo, 2024)
The low cognitive abilities of children at RA Tarbiyatul Ihsan regarding color recognition are indicated by their inability to group colors and match objects according to color, count/number and show number symbols. This is caused by the lack of interest in the media used by teachers in learning. Therefore, researchers intend to improve children's cognitive abilities through the game Dice Dance and Bola Blast in group B RA Tarbiyatul Ihsan Sumberasih. This research used the Class Action Research (PTK) method which was conducted on group B, totaling 15 students in the first semester of the 2023-2024 academic year. This research was conducted from December 2023 to January 2024. Data collection techniques used tests, interviews and observation. Done in 2 cycles. Each cycle is held in 3 meetings. This research was preceded by a pre-cycle, with a percentage of 32%, cycle I experienced an increase with a percentage of 52% and cycle II experienced an increase of 78.66%. It was concluded based on research that the Dice Dance and Ball Blast games can improve the cognitive abilities of group B children to improve children's development in recognizing colors, grouping and matching objects according to color, counting/counting and showing number symbols. Therefore, this game is suitable for educators to use to help children's cognitive development. Keywords: Cognitive Enhancement, Game Media, Dance Dice and Blast Ball